2010
DOI: 10.1002/ppp.705
|View full text |Cite
|
Sign up to set email alerts
|

Effects of scale and data source in periglacial distribution modelling in a high arctic environment, western Svalbard

Abstract: The effects of scale (modelling resolution) and sources of data were explored in relation to periglacial distribution modelling for an area on western Svalbard in the High Arctic. To assess the effects of scale on predictive performance, the distributions of sorted circles and solifluction lobes were modelled at two resolutions (20 × 20 m and 200 × 200 m) using a boosted regression tree, a novel statistical ensemble method. To analyse the effects of sources of data on periglacial distribution modelling, a gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 71 publications
(94 reference statements)
0
4
0
Order By: Relevance
“…Furthermore, collinearity effects were examined by calculating the Spearman's rank order correlation coefficient (e.g. Hjort et al, 2010) which showed no sign of an unacceptably high level of intercorrelation between the independent variables (all values <0.6). Finally, also the potential problem with spatial autocorrelation (i.e.…”
Section: Regression Analysismentioning
confidence: 99%
“…Furthermore, collinearity effects were examined by calculating the Spearman's rank order correlation coefficient (e.g. Hjort et al, 2010) which showed no sign of an unacceptably high level of intercorrelation between the independent variables (all values <0.6). Finally, also the potential problem with spatial autocorrelation (i.e.…”
Section: Regression Analysismentioning
confidence: 99%
“…Brenning et al , ; Hjort and Luoto, ), thus failing to consider the potentially important factors operating concurrently or the optimal resolution of the input data (e.g. Hjort et al , ; Etzelmüller, ; Potter, ).…”
Section: Introductionmentioning
confidence: 99%
“…13,[15][16][17] These automated classification methods allow for larger areas to be mapped more quickly while reducing human error (although introducing machine error), and facilitating comparable results and model transferability. 13,18 At regional scales, topographic parameters derived from digital elevation models (DEMs) are shown to be one of the primary predictors of landforms in periglacial environments, 13,19,20 particularly in high-Arctic environments because of the low abundance of vegetation. 19 Statistical analyses of remotely sensed topographic, optical and/or climate data landform classifications 21 use a range of multivariate and simple statistical techniques including generalized linear methods such as linear discriminant analysis (LDA), 13,22 logistic regression, 17 and artificial neural networks.…”
mentioning
confidence: 99%
“…13,18 At regional scales, topographic parameters derived from digital elevation models (DEMs) are shown to be one of the primary predictors of landforms in periglacial environments, 13,19,20 particularly in high-Arctic environments because of the low abundance of vegetation. 19 Statistical analyses of remotely sensed topographic, optical and/or climate data landform classifications 21 use a range of multivariate and simple statistical techniques including generalized linear methods such as linear discriminant analysis (LDA), 13,22 logistic regression, 17 and artificial neural networks. 13,23 Reported comparisons of different suites of statistical modeling suggest that simple models such as LDA and logistic regression perform equally when compared to more complex machine-learning techniques.…”
mentioning
confidence: 99%